2023
DOI: 10.3390/met13030489
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Mechanical Properties and Oxidation Behavior of 1.2 and 1.7 GPa Grades Coating-Free Press-Hardened Steels

Abstract: Al-Si-coated boron-alloyed steels are the most widely used press-hardened steels (PHSs), which offers good oxidation resistance during hot forming due to the presence of the near eutectic Al-Si coating. In this study, a recently developed novel un-coated oxidation resistant PHS, called coating-free PHS (CF-PHS), is introduced as an alternative to the commercial Al-Si coated PHSs. With tailored additions of Cr, Mn, and Si, the new steel demonstrates superior oxidation resistance with a sub-micron oxide layer af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The CF–PHS exhibits an oxide scale of less than 1 μm during the hot‐forming process at 900–950 °C, demonstrating excellent oxidation resistance and promising application prospects. [ 19 ] Some researchers have shown that adding Cr and Si to steel results in synergistic antioxidant effects, which improve the high‐temperature oxidation resistance of steel. Lim [ 20 ] reported that with the addition of Si to high‐Cr (12 wt%) Fe–Cr alloys, Si could serve as an efficient diffusion barrier by forming a localized Si‐oxide network beneath the Cr‐rich oxide layer.…”
Section: Introductionmentioning
confidence: 99%
“…The CF–PHS exhibits an oxide scale of less than 1 μm during the hot‐forming process at 900–950 °C, demonstrating excellent oxidation resistance and promising application prospects. [ 19 ] Some researchers have shown that adding Cr and Si to steel results in synergistic antioxidant effects, which improve the high‐temperature oxidation resistance of steel. Lim [ 20 ] reported that with the addition of Si to high‐Cr (12 wt%) Fe–Cr alloys, Si could serve as an efficient diffusion barrier by forming a localized Si‐oxide network beneath the Cr‐rich oxide layer.…”
Section: Introductionmentioning
confidence: 99%
“…The structural parts of automobile body usually deform and fracture under a stress state close to plane strain bending during vehicle crash. [15][16][17] Therefore, plane strain bendability is an important material property for hot-stamped steels. At present, the three-point bending test according to VDA 238-100 standard is widely accepted to assess the plane strain bendability of hot-stamped steels.…”
Section: Introductionmentioning
confidence: 99%
“…In actual automotive components, these two PHSs are usually required to be combined using laser welding followed by integral hot stamping, to obtain gradient performance parts, which can realize the combination of high strength-toughness [7]. Such integrated hot stamping of anti-intrusive PHS with high energy-absorbing PHS is widely used in tailor hot-stamped, laser-welded door rings [8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this hot stamping also exhibits good ductility of ~11.2% due to the introduction of the ferrite phase. Unfortunately, almost all studies on high-temperature oxidation resistance have focused on 1500~2000 MPa grade anti-intrusion PHSs, while related studies on energy-absorbing PHSs are extremely lacking, especially 1000 MPa high energyabsorbing PHSs, which are usually matched with 1500~2000 MPa anti-intrusion PHSs for integrated hot stamping to form gradient performance parts, such as tailor hot-stamped laser-welded door rings [7,8]. Therefore, to improve the overall antioxidant performance of the part, the oxidation resistance of 1000 MPa high energy-absorption PHS also needs to be emphasized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation